Education: 4. Perspectives on the Concepts of Gifting and Talent and How they are Used in the Arts - Anghel Ona Ionica (Sciendo, 2018)
The educational programs dedicated to gifted and talented people are developed or must be developed starting with an adhesion to a definition of the working concept, in this case "giftedness" or "talent". A foray into the literature proves that the meaning of the concept of giftedness has developed over time, as influenced by various factors such as historical (history of the research) and of human nature (psychological or educational). The aim of the paper is to make a review of the associated key moments in the evolution of the concept of giftedness. The bibliographical sources allowed us to achieve a chronological overview of the position/attitude of the most prestigious researchers in the field, who tried to explain the concept of giftedness and talent. The collected data demonstrates that there is no unanimous acceptance of a single definition until today, and that the concept keeps its tendency to perpetual transformation. The constant during this time remains its relationship with the demonstrated, respectively with the potential performance.